Analisis Pertumbuhan Ekonomi Inklusif di Provinsi Sulawesi Selatan Tahun 2010-2024 - Maulidan, Andi Reski Lailatul; Hastuti, Diah Retno Dwi; Alam, Syamsu; Astuty, Sri; Rajab, Abdul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The phenomenon of inclusive economic growth reflects the quality of regional development. This study aims to analyze the effect of poverty, income inequality (Gini ratio), Human Development Index (HDI), and Open Unemployment Rate (OUR) on inclusive economic growth in South Sulawesi Province. The data used is panel data from 24 districts/cities during the 2010–2024 period, sourced from the Central Statistics Agency and related agencies. The research method uses a quantitative approach, panel data regression analysis with a fixed effect model. The results show that poverty has no effect on inclusive economic growth, while the Gini ratio has a negative effect on inclusive economic growth. Meanwhile, HDI was found to have a positive effect, confirming that the quality of human development is key to achieving equitable growth. TPT has no effect on inclusive economic growth. The coefficient of determination in this study is 0.7889 or 78.89 percent of the ability of the independent variable to explain the dependent variable. Meanwhile, the remaining 21.11 percent is influenced by other factors outside the model.